Housing affordability among Generation Y in Malaysia a conceptual analysis / Amira Aishah Mohd Shoed and Geetha Subramaniam - Mohd Shoed, Amira Aishah; Subramaniam, Geetha (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2015)
Over the past few years, the house prices in Malaysia have experienced a huge value development and turned into a stress pattern for those who want to own a house, especially first time home buyers. This conceptual paper will examine issues of housing affordability among young Malaysians who have intentions of buying a house. The persistent increment of house prices have influenced the capability and ability of individuals to buy houses. The issue is extremely serious among the first time home purchaser, particularly the Generation Y. Thus, this paper will discuss some of the reasons behind this issue and also examine the current government housing policies which are in place to help home buyers. This conceptual study would form a theoretical framework for further empirical work to be done by future researchers and which can be used by policy makers and stakeholders in designing affordable housing for Generation Y in Malaysia.